Elementary School Management: Planning, Implementation and Supervision of Management - Fauziah, Amalia Kholisah; Maulidina, Anniar; Nurkhalifah, Siti; Mutiara, Liza; Pertiwi, Santhi (Jurnal Inovasi Pendidikan MH Thamrin, 2025)
Education is the main pillar of national development, and the success of the education system is highly dependent on the effectiveness of school management, including the supervision aspect. Supervision plays an important role in ensuring that educational activities run according to objectives, preventing various obstacles, and improving the quality of learning and teacher professionalism. Planning is the main foundation in effective and sustainable elementary school management. This study aims to examine the importance of planning in elementary education management and strategies that can be applied to improve its effectiveness. This study uses a literature study method by analyzing various sources such as books, journals, and scientific articles. The results of the study indicate that thorough planning—including determining the vision, mission, goals, targets, and strategies—plays an important role in improving the quality of learning, shaping student character, and supporting teacher professional development. SWOT analysis is also used as a strategic tool to evaluate the internal and external conditions of the school in order to formulate planning that is responsive to challenges and opportunities. These findings confirm that systematic and adaptive planning is the key to creating superior school management that is oriented towards improving the quality of education.